1985
DOI: 10.1039/c39850001166
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of (3S,4R)-eldanolide and (5S,12R)-leukotriene-B4 through photolysis of optically active hydroxy-7,7-dimethylbicyclo[3.2.0]heptanones

Abstract: Photoisomerisation of 3-hydroxy-7,7-dimethylbicyclo[3.2.0]heptan-6-ones is the key step in a new route to the pheromone eldanolide while leukotriene-B4 is available through a photolytic retro[2 + 21 reaction of 2-hydroxy-7,7-dimethyl bicyclo[3.2.0]heptan-6-ones. On photolysis, substituted cyclobutanones can undergo three transformations: (a) ring expansion to give an oxacarbene, (b) decarbonylation, or (c) retro[2 + 21 cycloaddition.1 When the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

1988
1988
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…Nach einigen Syntheseoperationen wurden die beiden Molekülteile zum Zielmolekül fusioniert. [148] Basierend auf derselben Strategie wurden die Naturstoffe (AE )-Goniothalamin, [149] (AE )-Argentilacton, [149] der (AE )-Streptomyces-L-Faktor [149] und (+)-Eldanolid [147,150] hergestellt. Die niedrige Ausbeute der in Schema 28 gezeigten Photoreaktionen (42 % für 96, 41 % für 98) ist zum Teil der nicht vollständig zu unterdrückenden Bildung von Oxacarbenen geschuldet, die ebenfalls durch das intramolekulare Nucleophil abgefangen werden können.…”
Section: Aufsätzeunclassified
“…Nach einigen Syntheseoperationen wurden die beiden Molekülteile zum Zielmolekül fusioniert. [148] Basierend auf derselben Strategie wurden die Naturstoffe (AE )-Goniothalamin, [149] (AE )-Argentilacton, [149] der (AE )-Streptomyces-L-Faktor [149] und (+)-Eldanolid [147,150] hergestellt. Die niedrige Ausbeute der in Schema 28 gezeigten Photoreaktionen (42 % für 96, 41 % für 98) ist zum Teil der nicht vollständig zu unterdrückenden Bildung von Oxacarbenen geschuldet, die ebenfalls durch das intramolekulare Nucleophil abgefangen werden können.…”
Section: Aufsätzeunclassified
“…Several syntheses for the natural (3S,4R)-isomer and the racemic mixture have been developed. [150][151][152][153][154][155] Recently, Devalankar et al obtained the lactone 140 by a regioselective ring opening of chiral epoxide 139 with Grignard chemistry (Fig. 18).…”
Section: Larger Macrocyclic Lactonesmentioning
confidence: 99%
“…Wakefield and coworkers reported that commencing from suitably functionalized bicycloheptanones, ring opening and intramolecular trapping of the derived alkenylketene provided viable routes towards natural products (+)-eldanolide (507) and (+)-leukotriene-B 4 (508) 225 . …”
Section: R=phmentioning
confidence: 99%